DEVELOPMENT OF A GUIDED INQUIRY-BASED BIOLOGY MODULE FOR TEACHING THE HUMAN REPRODUCTIVE SYSTEM FOR GRADE XI STUDENTS AT SMA NEGERI 1 NA IX X - Dewi Triana; Harahap, Hasmi Syahputra; Khairul (Pena Cendekia Insani, 2025)
This study aims to develop a guided inquiry-based biology learning module on the reproductive system material for grade XI SMA/MA. This research is a type of research and development (Research and Development or can also be called R&D). Research and Development (R&D) is one of the research models used to produce a specific product from a problem and test the effectiveness of the product. The results of product validation and trials indicate that the guided inquiry-based biology learning module on the reproductive system material for grade XI SMA/MA obtained qualifications with a validation level of